Blackwell Publishing Ltd. Herbal medicine induced Stevens–Johnson syndrome: a case report - A. D. CHOWDHURY, M. ODA, A. F. MARKUS, T. KIRITA, & C. R. CHOUDHURY (Paediatric Dentistry, 2004)
A severe form of Erythema Multiforme (EM) known as Stevens–Johnson syndrome (SJS) is characterized by acute mucocutaneous and epidermal desquamation of the tissues of the skin, mucocutaneous surfaces and the eye [1].